The Impact Of Rice Field Productivity On Changes In Paddy Field Areas (LBS) In Indonesia - Betharia W M Pangaribuan; Vid Adrison (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study analyzes the impact of rice field productivity and other factors on changes in paddy field area (LBS) at the regency/city level in Indonesia. Using panel data from 364 regencies/cities (2010–2022), LBS changes are measured as the average annual percentage change over two periods: 2013–2019 and 2019–2023. To address endogeneity in rice productivity, a two-stage Instrumental Variable (IV) method with fixed effects is applied. The first stage instruments productivity with rainfall and previous productivity, while the second stage assesses its impact alongside control variables, including the agricultural, real estate, and construction sectors, population density, and a Dummy Policy Variable for LP2B protection with lag effects up to three years. Results indicate that rice productivity and other factors are not significant predictors of LBS changes, likely due to land ownership inequality and measurement errors. A restricted sample further suggests that LP2B protection is ineffective in preserving LBS. Using Local Average Treatment Effect (LATE), the IV method estimates policy impacts for regions aligned with instrument variation. The study recommends accelerating land redistribution, certification, technical support, and stricter enforcement at both central and regional levels to safeguard paddy fields.